Produção de passas de talo de abacaxi pérola por processo osmo-solar - Falcao Filho, Ronaldo dos Santos (2011)
The objective of the present work was to produce pineapple stem raisin by means of osmo-solar drying. The raw material was selected taking into account parameters such as: color of the rind and level of soluble solids from the fruits. A type 23 factorial design was preceded with 4 repetitions at the central point, for further optimization of the osmotic dehydration using the methodology of surface responses. The partially dry product obtained from the osmotic dehydration, utilizing as conditions the ones from the planning, passed through complementary sun drying by means of a solar drier, build with assessable materials such as joined wood, aluminum plates, glass boards, matte black paint, Styrofoam and coal. The raw material, the product partially dehydrated and the final product had their compositions analyzed. The evaluation of the dimensions of the pineapples showed little variation, with a CV < 10%, an important factor for the standardization and control of the industrial processes. The raw material also presented a high level of soluble solids and low level of acidity, proving the analyzed pineapple useful for in natura consumption and for the industrial processing of several products, among them alcoholic and non-alcoholic beverages. Furthermore, the raw material has proven to be an excellent source of vitamin C, with a concentration of such nutrient higher than what is daily recommend according to legislation. The adopted linear factors have presented themselves to be adequate, they were fairly adjusted and predictive for the loss of (PA) and weight loss (PP) and fairly adjusted and predictive to gain of solids and gain of solid-loss of water ratio (GS:PA). Analyzing the level curves and surface of answer of the optimization parameters GS:PA, built from the statistical models, it was determined the ideal conditions of osmotic dehydration which were: T = 50 ºC, C = 40 g 100 g-1 and F:SO= 3:20. In evaluation, the Sun dryer presented and average temperature of 41.2 ºC against 35.7 ºC of natural air and maximum temperature of 46 ºC, besides the minimal relative air humidity of 37%. The product obtained after the draught presented humidity of 13.70 g 100 g-1 obeying the legislation concerning the maximum levels of humidity for dehydrated fruit.